Measurement of semileptonic branching fractions of B mesons to narrow D** states - Abazov, V. M. (2005)
Using the data accumulated in 2002-2004 with the D0 detector in proton-antiproton collisions at the Fermilab Tevatron collider with a center-of-mass energy of 1.96Â TeV, the branching fractions of the decays Bâ†'DÂ10(2420)Î+ÎÎX and Bâ†'DÂ2*0(2460)Î+ÎÎX and their ratio have been measured: B(bÂâ†'B)Ã- B(Bâ†'DÂ10Î+ÎÎX)Ã- B(DÂ10â†'D*-Ï€+)=[0.087Â±0. 007(stat)Â±0.014(syst)]%; B(bÂâ†'B)Ã- B(Bâ†'DÂ2*0Î+ÎÎX)Ã- B(DÂ2*0â†'D*-Ï€+)=[0. 035Â±0.007(stat)Â±0.008(syst)]% and [B(Bâ†'DÂ2*0Î+ÎÎX) Ã-B(DÂ2*0â†'D*-Ï€+)]/ [B(Bâ†'DÂ10Î+ÎÎX)Ã- B(DÂ10â†'D*-Ï€+)]=0.39Â±0. 09(stat)Â±0.12(syst), where the charge conjugated states are always implied. © 2005 The American Physical Society.